A review on the green synthesis of hierarchically porous zeolite. (September 2020) - Maghﬁrah, A.; Ilmi, M.M.; Fajar, A.T.N.; Kadja, G.T.M.
Abstract: Conventional bottom-up and top-down methods for synthesizing hierarchical zeolite have led to complicated economic and environmental issues due to the requirement of expensive and hazardous organic molecules, the large amount of acid/base solution, high energy, and expensive starting materials. Besides, the bottom-up method through the hydrothermal crystallization evokes safety issues due to the high autogenous pressure. Accordingly, considerable efforts have been made to develop green route synthesis of hierarchical zeolite by eliminating the use of a solvent (solvent-free), utilizing sustainable starting materials and green secondary template (mesoporogen), as well as eliminating the use of mesoporogen (mesoporogen-free). Other routes, including recycling of mother liquor, steam-assisted conversion, gel-like-solid phase method, and silanization, are also elaborated, as they are reported to promote a green and facile approach for the synthesis of hierarchical zeolites. In this review, we provide recent progress on the development of the green synthesis of hierarchically porous zeolite. Graphical abstract: Image 1 Highlights: Several types of green synthesis approach of hierarchical zeolites are discussed. The combination of two or more green synthesis techniques further increases the efficiency. Hierarchical pore architecture eliminates diffusion limitation in catalysis application. The search of new green synthesis approach should also be considered. It is of significant importance to realize green synthesis of hierarchical zeolite in industrial scale.